EL DEBATE SOBRE LA IMPRENTA EN LA REPÚBLICA DE LAS LETRAS. TRIBUTOS, QUERELLAS, Y LOS PROYECTOS DE LOS ERUDITOS PARA REFORMAR EL ARTE TIPOGRÁFICO EN LA ESPAÑA DEL SIGLO XVIII - Albert Corbeto López (Cuadernos de Ilustración y Romanticismo)
Since the advent of printing the Republic of Letters was inexorably linked with typographic technology, despite the negative effects that for the scholars had the conversion of the book into a mass product subject to the profit of booksellers and printers. This study offers an approach to the ambivalent relationship that men of letters had with the printing press, with the aim of place in context the various attempts that in eighteenth century Spain intended to restore the printing press thanks to the initiative of some enlightened people concerned with the state of degradation of book arts.